(untitled) (Academicia Globe: Inderscience Research, 2022)
This paper aims to know the direct role of morphine in postpartum pain relief of Iraqi Women A systematic study was established consisting of two groups of patients and control, where patients were collected from different hospitals in Iraq. The group of patients consisted of 30 patients, while as for the control group it was 15 patients Patients were assessed based on the amount of oral pain relievers required, and a visual analog scale (VAS) sensitive enough to measure pain was used and the VAS data correlates well with other methods of measuring pain intensity.Role morphine to decrease complication Nausea according to VAS, where we notice a decrease in symptoms and a noticeable improvement by 40%, and the same is the case in relieving headache pain, but the percentage of improvement increased and became 60%, but this does not mean we can take morphine at any time and in final we concluded in this study that morphine helps to reduce the intake of pain relievers that are taken orally.